Aerobic fitness is associated with greater white matter integrity in children - Chaddock-Heyman, Laura; Erickson, Kirk I.; Holtrop, Joseph L.; Voss, Michelle W.; Pontifex, Matthew B.; Raine, Lauren B.; Hillman, Charles H.; Kramer, Arthur F. (Frontiers in Human Neuroscience, 2014)
Aerobic fitness has been found to play a positive role in brain and cognitive health of children. Yet, many of the neural biomarkers related to aerobic fitness remain unknown. Here, using diffusion tensor imaging (DTI), we demonstrated that higher aerobic fitness was related to greater estimates of white matter microstructure in children. Higher fit 9- and 10-year-old children showed greater fractional anisotropy (FA) in sections of the corpus callosum, corona radiata, and superior longitudinal fasciculus, compared to lower fit children. The FA effects were primarily characterized by aerobic fitness differences in radial diffusivity (RD), thereby raising the possibility that estimates of myelination may vary as a function of individual differences in fitness during childhood. White matter structure may be another potential neural mechanism of aerobic fitness that assists in efficient communication between gray matter regions as well as the integration of regions into networks.